The Use of Probing Prompting Learning (PPL) and Inside Outside Circle (IOC) Model to Learning Outcome of Plane Figure Material - Marceillina, Dian Novita; Wiryokusumo, Iskandar; Walujo, Djoko Adi (International Journal of Educational Technology and Learning, 2019)
This study aims to discover: (1) the difference of the learning outcomes of plane (geometry) material between the use of Probing Prompting Learning (PPL) model and Inside Outside Circle (IOC) model; (2) the difference of the learning outcomes of plane figure material between students with high prior knowledge and students with low prior knowledge; (3) the influence of the interaction between the models and students’ prior knowledge towards the learning outcomes of plane figure material. This study uses true experimental design as the research design. The population of the study consists of students from two elementary school in Surabaya in total of 134 students. The instruments used in this study are the prior knowledge test and the learning result test. The data analysis method used to test and to verify the hypotheses was two-way ANOVA test. The result of the study indicates that: (1) there is a difference in the learning outcomes of plane figure material between the PPL model and the IOC model; (2) there is a difference in the learning outcomes of plane figure material for students with high prior knowledge and low prior knowledge; (3) there is a correlation between the model and prior knowledge towards the learning outcomes of plane figure material.